Proposed diagnostic criteria for acute‐on‐chronic liver failure in Japan. Issue 4 (2nd March 2018) - Mochida, Satoshi; Nakayama, Nobuaki; Ido, Akio; Inoue, Kazuaki; Genda, Takuya; Takikawa, Yasuhiro; Sakaida, Isao; Terai, Shuji; Yokosuka, Osamu; Shimizu, Masahito; Takikawa, Hajime
Abstract : To establish diagnostic criteria for acute‐on‐chronic liver failure (ACLF) in Japan, the Intractable Hepato‐Biliary Disease Study Group of Japan undertook a multicenter pilot survey for patients fulfilling the Asian Pacific Association for the Study of the Liver (APASL), Association for the Study of the Liver–Chronic Liver Failure (EASL‐Clif) Consortium, or Chinese Medical Association (CMA) diagnostic criteria for ACLF. The APASL criteria were suitable for screening Japanese patients with ACLF when patients whose conditions were triggered by gastrointestinal bleeding were included within the disease entity, and the EASL‐Clif Consortium criteria were useful for classifying the severity of the patients' conditions. Based on these observations, the Study Group proposed the following diagnostic criteria for ACLF in Japan: patients with cirrhosis and a Child–Pugh score of 5–9 should be diagnosed as having ACLF when a deterioration of liver function (serum bilirubin level ≥5.0 mg/dL and prothrombin time value ≤40% of the standardized values and/or international normalization rate ≥1.5) caused by severe liver damage develops within 28 days after acute insults, such as alcohol abuse, bacterial infection, gastrointestinal bleeding, or the exacerbation of underlying liver diseases. The severities of the patients can be classified into four grades depending on the extent of the deterioration in organ functions, including kidney, cerebral, blood coagulation, circulatory and respiratory functions, as well as liver function. The usefulness of these novel criteria should be validated prospectively in a large‐scale cohort in the future.